Learning Model Service-Learning at Boarding School - Moch. Sya'roni Hasan (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2021)
This study aims to describelearning learning servicecarried out at Pondok Pesantren Al Urwatul Wutsqo Jombang. This study used a qualitative approach with case study design. Data was collected using in-depth interviews, participatory observation, and documentation. Data analysis techniques include data collection, data condensation, data presentation, and drawing conclusions, checking the validity of the findings by extending participation; source triangulation techniques, theories, and methods; and persistence of observation. Research informants are pesantren caregivers, ustadzah, students and the community. The results showed that: first, the steps of service learning that were applied at Pondok Pesantren al Urwatul Wutsqo Jombang and Darussalam Sumbersari Kediri, among others: 1). Intention, 2). Curriculum integration, 3). Preparation includes; debriefing and selection ofparticipants service learning, determining the place of service-learning service, division of groups and accompanying teachers, departure ofparticipants service learning, 4). Implementation of service learning, 5). Meditation/contemplation, 6). Evaluation of service learning, and 7). Closing of service learning.